'A matter for conjecture': leucotomy in Western Australia, 1947–70. Issue 2 (June 2018) - Martyr, Philippa; Janca, Aleksandar
Very little has been published on the rise and fall of psychosurgery in Australia. In the mid-twentieth century, Western Australia was the largest but most sparsely-populated of the six Australian States, and its local psychiatry practice was, as one commentator put it, 'backward'. Nonetheless, electroconvulsive therapy was introduced in 1945, and leucotomy in 1947. This paper will explore the introduction of leucotomy to Western Australia in the context of wider national and international trends in psychiatry, and posit some reasons for its decline and abandonment in the 1970s. It will present a narrative reconstruction of the local introduction and practice of leucotomy, using retrieved, reconstructed and previously unpublished data.